2021
DOI: 10.48550/arxiv.2105.05730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Greybody factor for an electrically charged regular-de Sitter black holes in $d$-dimensions

Md Sabir Ali,
A. Naveena Kumara,
Kartheek Hegde
et al.

Abstract: In this article, we study the propagation of scalar fields in the gravitational background of a spherically symmetric, electrically charged, regular-de Sitter black holes in higher dimensions. We carry out a thorough investigation of the grey body factors, by deriving analytical expressions for both minimally and non-minimally coupled scalar fields. Then we study the profile of grey body factors in terms of particle properties, namely the angular momentum quantum number and the non-minimal coupling constant, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…We have extended this work for modified charged AdS BH and discussed the effects of physical parameters on GBF. The GBF for a regular de Sitter BH coupled (minimally/non-minimally) with non-linear charge is analyzed in [34]. We have found that the effective potential of the BH increases with an increase in both the mass and electric charge parameters (q m and q e ).…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…We have extended this work for modified charged AdS BH and discussed the effects of physical parameters on GBF. The GBF for a regular de Sitter BH coupled (minimally/non-minimally) with non-linear charge is analyzed in [34]. We have found that the effective potential of the BH increases with an increase in both the mass and electric charge parameters (q m and q e ).…”
Section: Final Remarksmentioning
confidence: 99%
“…The absorption rate of BH for non-minimally coupled massless scalar field with strings was studied in [33]. Ali et al [34] studied the GBF of a spherically symmetric charged regular de Sitter BH in higher dimensions. They found that the non-minimal coupling reduces the GBF while the non-linear charge increases the GBF.…”
Section: Introductionmentioning
confidence: 99%